The Tribal Areas under the Administration of the West Pakistan Province - Gul, Asma; Minhaj-ul-Hassan, Syed (The Journal of Humanities & Social Sciences, 2023)
Tribal Areas of Khyber Pakhtunkhwa, Pakistan (FATA, PATA and Frontier Region) are now-a-days under focus in national and international geo-political strategies. To avoid any future disturbance in the region after Pakistan army’s operation Zarb-e-Azb, suggestions are circulating of amalgamating this region with the province of Khyber Pakhtunkhwa or creating a new province comprising of the said areas. But very few of us know that in the past it remained part of a province which was the province of West Pakistan (1955-1970) comprised of all the territories of today’s Pakistan. The Province of West Pakistan, for administrative purpose, was divided into Divisions. The former province of North-West Frontier was comprised of two Divisions: Peshawar and Dera Ismail Khan under the charge of Commissioners. At the dissolution of West Pakistan Province (March 1970) three provinces of the region were reinstated and Balochistan was created as a full-fledged province as well and only the Tribal Area of North West was returned to the Federal authority.